Measuring Local Government Financial Performance With Financial Ratios - Purba, Sahala; Purba, Rani Agustines; Simangunsong, Lucyanna Yosephine; Gultom, Nadia A.V.E.; Sinaga, Agnes Patricia R. (JAS (Jurnal Akuntansi Syariah), 2024)
This research aims to analyze the financial performance of local government in the Toba Regency. The data source uses secondary data in the form of Toba Regency government financial reports for 2020-2022. Data were analyzed using a quantitative descriptive approach. The financial performance of the Toba Regency government is measured using eight financial ratios. The results of the research show that the financial performance of the Toba Regency government in terms of regional financial independence, regional financial dependence, and the degree of fiscal decentralization obtained meagre results. The level of effectiveness of local original revenue (LOR) and the effectiveness of local taxes obtained very effective results. The level of LOR efficiency and regional tax efficiency obtained very efficient results. The degree of contribution of regionally owned enterprises (ROEP) resulted in low contribution results. Overall, the Toba Regency needs to improve at implementing and managing finances. This research can be a reference for the Toba Regency government in improving financial performance through eight financial ratios so that budget use is effective and efficient.